Relative frequency of headache types: a longitudinal study in the tertiary care - Ariovaldo Alberto da Silva-Júnior; Bruno Engler Faleiros; Tales Michel dos Santos; Rodrigo Santiago Gómez; Antônio Lúcio Teixeira (Arquivos de Neuro-Psiquiatria)
In order to properly assess patients with primary headache, one needs to follow the cases up longitudinally. In Brazil, there were no studies using this methodology published after the publication of the latest issue of the International Classification of Headaches in 2004 - ICHD-2. This is especially important when we consider that it was only after such publication that we had the criteria used to classify some types of headaches which evolve with daily, or almost daily, spells, and which are very common in tertiary health care centers. OBJECTIVE: To assess the frequency of headache types in a tertiary health care center, in a longitudinal fashion. METHOD: We assessed 95 consecutive patients. These patients were diagnosed and classified according to the ICDH-2. The subjects were followed up for 18 months, they were treated and reassessed. RESULTS: Most of the individuals had more than one type of headache. Among those with episodic migraine in 2007, 6 developed chronic migraine in 2008, producing an incidence rate of 7.2%. Among those with chronic migraine in 2007, 9 remitted, producing a remission rate of 75%. In 2007, 24 individuals abused analgesic agents and 17 no longer showed abuse criteria in 2008 - when 7 new cases were found. CONCLUSION: The diagnosis of migraine remained stable. On the other hand, treatment brought about a reduction in the frequency of headaches caused by excessive use of analgesic, although the frequency of daily chronic headache was almost unaltered.